Microbial Fabricated Nanosystems: Applications in Drug Delivery and Targeting - Sachin, Kumar; Karn, Santosh Kumar (Frontiers in Chemistry, 2021)
The emergence of nanosystems for different biomedical and drug delivery applications has drawn the attention of researchers worldwide. The likeness of microorganisms including bacteria, yeast, algae, fungi, and even viruses toward metals is well-known. Higher tolerance to toxic metals has opened up new avenues of designing microbial fabricated nanomaterials. Their synthesis, characterization and applications in bioremediation, biomineralization, and as a chelating agent has been well-documented and reviewed. Further, these materials, due to their ability to get functionalized, can also be used as theranostics i.e., both therapeutic as well as diagnostic agents in a single unit. Current article attempts to focus particularly on the application of such microbially derived nanoformulations as a drug delivery and targeting agent. Besides metal-based nanoparticles, there is enough evidence wherein nanoparticles have been formulated using only the organic component of microorganisms. Enzymes, peptides, polysaccharides, polyhydroxyalkanoate (PHA), poly-(amino acids) are amongst the most used biomolecules for guiding crystal growth and as a capping/reducing agent in the fabrication of nanoparticles. This has promulgated the idea of complete green chemistry biosynthesis of nano-organics that are most sought after in terms of their biocompatibility and bioavailability.